Two virulent bacteriophages targeting carbapenem-resistant Raoultella planticola - Hoang, Cuong V.; Fan, Jonathan; Bhasin, Lauren; Del Mundo, Anthony; Law, Vanessa; Nguyen, Dominic; Ganiger, Suraj; Mansour, Ashley; McElheny, Christi L.; Doi, Yohei; Olawole, Olakunle I. (Frontiers in Microbiology, 2026)
Carbapenem-resistant Raoultella planticola (CRRP) is an emerging nosocomial pathogen with limited therapeutic options. Here, we describe the comparative characterization of two novel virulent bacteriophages, Macy and Sally, both isolated from the same soil microenvironment. Macy exhibits exceptional lytic potency, with a burst size of 8,375 PFU per infected cell, narrow host specificity, and pronounced biofilm-disrupting activity likely mediated by a putative depolymerase. In contrast, Sally displays a broader host range, infecting both R. planticola and R. ornithinolytica (including a clinical CRRP isolate), while maintaining moderate lytic activity, notable acid tolerance, and substantial biofilm reduction. SNP analysis revealed that resistant isolates carried mutations in genes linked to surface polysaccharide biosynthesis and LysR-family transcriptional regulation, conferring resistance at a measurable cost to bacterial growth fitness. Genomic and phylogenomic analyses further revealed distinct evolutionary trajectories: Macy is a large (147.8 kb) member of Straboviridae Straboviridae with a mosaic genome related to Raoultella phages, whereas Sally is a compact (48.5 kb) Casjensviridae phage that is siphovirus more closely aligned with Klebsiella and Enterobacter phages. Pangenomic comparisons highlighted Macy’s strain-specific gene expansions versus Sally’s cross-genus homology, emphasizing divergent adaptation strategies. Together, these findings illustrate the complementary therapeutic potential of Macy and Sally and establish a genomic and phenotypic foundation for developing effective phage cocktails against multidrug-resistant Raoultella infections.